The effect of HIIT on body composition, cardiovascular fitness, psychological well-being, and executive function of overweight/obese female young adults - Guo, Linxuan; Chen, Jiaying; Yuan, Wenxue (Frontiers in Psychology, 2023)
Purpose: To evaluate the effect of a short-term HIIT program on the selected health-related parameters for female young adults with overweight/obesity in a university context. Methods: 48 participants were randomly divided into two groups. The exercise group (HIIT) received a HIIT intervention of aerobics for four weeks, while the control group (CON) received no training. Body composition including waist circumference (WC), body fat percentage (BF%), Cardiorespiratory fitness (VO2max), the score of Self-Rating Depression Scale (SDS), and Stroop word-color test (SCWT) results were assessed before and after the intervention along with within- and between-group comparisons. Results: All the indices were significantly improved in HIIT group (P < 0.01) after 4 weeks of intervention. No significant changes were found in CON. There were significant differences between HIIT and CON in cardiovascular fitness (P < 0.01), SDS (P < 0.01) and SCWT (P < 0.05) before and after 4 weeks. In addition, weekly measurements of HIIT effects showed significant changes (P < 0.01) from the second week in the variables of body composition, VO2max, SDS and SCWT when compared with the baseline and maintained the tendency till the end of program. Conclusion: The short-term HIIT aerobics of campus program conducted in non-lab setting induced significant improvements in body composition, cardiovascular fitness, psychological well-being and executive function in young female adults with overweight.